2016
DOI: 10.1021/acs.jafc.6b03464
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Fungicidal Activity, and Unexpected Docking Model of the First Chiral Boscalid Analogues Containing Oxazolines

Abstract: Chirality greatly influences the biological and pharmacological properties of a pesticide and will contribute to unnecessary environmental loading and undesired ecological impact. No structure and activity relationship (SAR) of enantiopure succinate dehydrogenase inhibitors (SDHIs) was documented during the structure optimization of boscalids. On the basis of commercial SDHIs, oxazoline natural products, and versatile oxazoline ligands in organic synthesis, the first effort was devoted to explore the chiral SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 22 publications
2
91
0
2
Order By: Relevance
“…In recent research, 1H‐pyrrole‐2‐carboxylic acid showed the significant activity of Pseudomonas by inhibiting QS and virulence determinants of P. aeruginosa PAO1 at the molecular level, which provides a useful scaffold for synthesis and construction of novel anti‐virulence drugs derived from natural sources (Ramadan et al ). A pyrrole compound developed by Syngenta, has been used for seed dressing and plant disease control (Li et al ). Amide compounds and their derivatives have attracted widespread attention in relation to their bacteriostasis and insecticidal aspects.…”
Section: Discussionmentioning
confidence: 99%
“…In recent research, 1H‐pyrrole‐2‐carboxylic acid showed the significant activity of Pseudomonas by inhibiting QS and virulence determinants of P. aeruginosa PAO1 at the molecular level, which provides a useful scaffold for synthesis and construction of novel anti‐virulence drugs derived from natural sources (Ramadan et al ). A pyrrole compound developed by Syngenta, has been used for seed dressing and plant disease control (Li et al ). Amide compounds and their derivatives have attracted widespread attention in relation to their bacteriostasis and insecticidal aspects.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo antifungal activity was determined on tomato fruits ( Lycopersicum esculentum ) infected by B. cinerea . Appropriate amounts of the tested compounds were dissolved in DMSO and then suspended in distilled water (containing 0.1% Tween 80) at a test concentration of 0.4 mg mL −1 .…”
Section: Methodsmentioning
confidence: 99%
“…The in vivo antifungal activity was determined on tomato fruits (Lycopersicum esculentum) infected by B. cinerea. 37 Appropriate amounts of the tested compounds were dissolved in DMSO and then suspended in distilled water (containing 0.1% Tween 80) at a test concentration of 0.4 mg mL −1 . Healthy fruits, which had been washed and treated with 75% aqueous ethanol in advance, were sprayed and the mixture evaporated under an ambient environment (∼ 28 ∘ C).…”
Section: In Vivo Antifungal Activitymentioning
confidence: 99%
“…Perhaps, this ‘de‐aromatization’ tends to optimize the hydrophobic moiety. Recently, the first exploration of chiral nicotinamides (boscalid analogues containing oxazolines) for the discovery of novel SDH‐inhibiting fungicides has been discussed . The SDH enzyme (succinate ubiquinone oxidoreductase; EC 1.3.5.1) is a mitochondrial hetero‐tetramer composed of four nuclear‐encoded subunits .…”
Section: Fungicidesmentioning
confidence: 99%
“…Recently, the first exploration of chiral nicotinamides (boscalid analogues containing oxazolines) for the discovery of novel SDH-inhibiting fungicides has been discussed. 51 The SDH enzyme (succinate ubiquinone oxidoreductase; EC 1.3.5.1) is a mitochondrial hetero-tetramer composed of four nuclear-encoded subunits. 52 The SDHA and SDHB subunits are exposed to the matrix of the mitochondria and SDHC and SDHD, which display a high degree of variation across species, are integral membrane proteins anchoring the SDHAB dimer to the integral membrane of the mitochondria.…”
Section: Fungicidal Succinate Dehydrogenase Inhibitorsmentioning
confidence: 99%